Open AccessOriginal Article Frequency of Common Nerve Injuries in Patients with Oral and Maxillofacial Trauma - Dildar, Zahid; Ishaq, Muhammad; Khan, Ali Akhtar; Ullah , Shafi; Yasir, Ammar; Mahmood, Tariq (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency of common nerve injuries in patients with maxillofacial trauma and to compare the frequency of sensory and motor nerve dysfunction in these patients.Study Design: Prospective longitudinal studyPlace and Duration of Study: Oral and Maxillofacial Surgery Department, Armed Forces Institute of Dentistry (AFID), Rawalpindi, Pakistan from Mar to Dec 2023.Methodology: A total of 190 patients with oral and maxillofacial trauma were reported to the Oral and Maxillofacial Surgery Department of the Armed Forces Institute of Dentistry. The study was conducted after approval from the Ethical Committee of the Armed Forces Institute of Dentistry.Results: Out of 190 individuals, 176(92.6%) were male and 14(7.3%) were female. Whereas 72 patients (37.8%) presented with trigeminal nerve injury, and 118 patients (62.2%) did not. Out of the nerve injury patients, 16(22.2%) had ophthalmic sub-branch injury, 22(30.5%) had maxillary nerve injury, and 34(47%) had mandibular nerve injury. 4 patients (2.1 %) with peripheral facial nerve injury and 186 patients (97.9%) without facial nerve injury were identified.Conclusion: The majority of maxillofacial trauma patients were young.   Males significantly suffered more from oral and maxillofacial trauma as compared to females. The trigeminal nerve was damaged more as compared to the facial nerve in these craniofacial trauma patients.